Persistenze, transizioni e problematiche storiografiche tra Spagna e Italia (secc. XVI-XXI). Una relazione che dura un’eternità? - Pilo, Rafaella; Scroccu, Gianluca (SocietàMutamentoPolitica, 2015)
The objective of this paper is to highlight reasons and effects of the longue durée on the close relationship that linked Italian and Spanish nations. We aim at focusing on changes, but also on the resistance of this relationship based on a dynamic process able to include continuity and transitions in European history and, then, gradually, in the global dimension. Our main purpose is to specify the long and variable trend of the relationships between the two nations during six centuries, starting from the sixteenth - the very beginning of the Spanish hegemony in the Mediterranean area - and continuing until nowadays and present time’s challenges. The essay, finally, aims at answering, even in a partial and necessarily incomplete way, a key question: after a long (“eternal”?) history in common, can we find a shared identity between persistence and abrupt transitions?